Engineering conductive protein films through nanoscale self-assembly and gold nanoparticles doping. Issue 14 (1st April 2021) - Mejias, Sara H.; López-Martínez, Elena; Fernandez, Maxence; Couleaud, Pierre; Martin-Lasanta, Ana; Romera, David; Sanchez-Iglesias, Ana; Casado, Santiago; Osorio, Manuel R.; Abad, Jose M.; González, M. Teresa; Cortajarena, Aitziber L.
Abstract : We report the fabrication of a conductive biomaterial based on engineered proteins and patterned gold nanoparticles to overcome the challenge of charge transport on macroscopic protein-based materials. This approach has great value for bioelectronics. Abstract : Protein-based materials are usually considered as insulators, although conductivity has been recently shown in proteins. This fact opens the door to develop new biocompatible conductive materials. While there are emerging efforts in this area, there is an open challenge related to the limited conductivity of protein-based systems. This work shows a novel approach to tune the charge transport properties of protein-based materials by using electron-dense AuNPs. Two strategies are combined in a unique way to generate the conductive solid films: (1) the controlled self-assembly of a protein building block; (2) the templating of AuNPs by the engineered building block. This bottom-up approach allows controlling the structure of the films and the distribution of the AuNPs within, leading to enhanced conductivity. This work illustrates a promising strategy for the development of effective hybrid protein-based bioelectrical materials.